Overlap syndromes atypical manifestations of Autoimmune Hepatitis - Leuschner, U. (Dr.Falk Pharma Gmbh, 2008)
This book explains about autoimmune liver diseases that included autoimmune hepatitis (AIH), at the time still known as chronic aggressive or active hepatitis, primary biliary cirrhosis (PBC) and primary sclerosing cholangitis (PSC).